2011
DOI: 10.1167/11.10.10
|View full text |Cite
|
Sign up to set email alerts
|

A novel method for analyzing sequential eye movements reveals strategic influence on Raven's Advanced Progressive Matrices

Abstract: Eye movements are an important data source in vision science. However, the vast majority of eye movement studies ignore sequential information in the data and utilize only first-order statistics. Here, we present a novel application of a temporal-difference learning algorithm to construct a scanpath successor representation (SR; P. Dayan, 1993) that captures statistical regularities in temporally extended eye movement sequences. We demonstrate the effectiveness of the scanpath SR on eye movement data from part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
162
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(182 citation statements)
references
References 52 publications
18
162
2
Order By: Relevance
“…Indeed, our present results and previous results suggest that the so-called "scalar prediction error signal" may be more of a vector-valued signal, as required by a number of RL extensions such as learning of successor representations (Dayan, 1993;Hayes et al, 2011), factored representations (Koller and Parr, 1999), and HRL (Barto and Mahadevan, 2003;Botvinick et al, 2009). However, this raises the problem of spatial credit assignment: how are the different prediction error signals distinguished in downstream areas to learn separate reward predictions?…”
Section: Discussionsupporting
confidence: 67%
“…Indeed, our present results and previous results suggest that the so-called "scalar prediction error signal" may be more of a vector-valued signal, as required by a number of RL extensions such as learning of successor representations (Dayan, 1993;Hayes et al, 2011), factored representations (Koller and Parr, 1999), and HRL (Barto and Mahadevan, 2003;Botvinick et al, 2009). However, this raises the problem of spatial credit assignment: how are the different prediction error signals distinguished in downstream areas to learn separate reward predictions?…”
Section: Discussionsupporting
confidence: 67%
“…The importance of the role of the relations between individual items is almost universally accepted in the analogy-making community. We believe that item-to-item saccades reveal the collecting of this relational information, a point of view also endorsed by Salvucci and Anderson (2001), Thibaut et al (2011), Hayes, Petrov, andSederberg (2011), and others.…”
Section: Mds Scatterplots Of Children's and Adults' Scanpathssupporting
confidence: 57%
“…This study was conducted in a larger context of several related experiments that combined think-aloud verbal protocols and eye tracking to investigate the role of strategic cognitive control during visual relational reasoning on Raven's APM (Hayes, 2015;Hayes et al, 2011. These experiments involved multiple sessions and various manipulations from Session 2 onward, but the first session was always the same: To establish a common baseline, eye-tracking and think-aloud protocols were collected while the participants worked on 14 Raven problems as detailed below.…”
Section: Methodsmentioning
confidence: 99%
“…This study is based exclusively on data from this common baseline session. Although other aspects of this large and multifaceted data set have been published elsewhere (Hayes et al, 2011, the pupillometric and verbal protocol aspects are reported here for the first time.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation